Large-Scale Urban Prototyping for Responsive Cities: A Conceptual Framework - Buš, Peter (Frontiers in Digital Humanities, 2019)
Despite ubiquitous urbanization and worldwide standardization, there is a lack of better differentiation between cities towards more customized environments. Although current advancements in computational design and digital fabrication technologies have been successfully applied in various architectural scales, they have rarely, if ever, been implemented in a larger urban context that can lead to broader benefit and responses for citizens. This research aims to describe the potential of digital fabrication methods for large-scale urban applications that can subsequently lead to more diverse and unique urban environments. This paper summarizes state-of-the-art principles for large-scale building construction that have been implemented in the past, along with current research and practice, and outlines a conceptual framework for possible future directions for large quantities of automatic and bespoke construction deliveries for future customized urban scenarios. This article also outlines the effects of end-users’ participation on urban developments using online users’ interface to inform building processes. To address aspects of end-users’ engagement in customization of cities, the article elaborates the question of responsiveness, where the citizen actively interacts with the environment and building technology and vice versa in order to customize the urban space. This is theoretically and conceptually explained and illustrated in a case study related to the formerly industrial harbor area of Tanjong Pagar in the city of Singapore, which is a test-bed for new urban developments on 325 ha of waterfront land in the downtown port area within the context of a tropical city.